(3GdTQW GdeGfY ef GdJUQa (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdhVYj hGdabg GdESdGej (B/ s - (3EjfGS eMeO EHQGgje LGO GdMbs; (3eMeO fLjH YhVjf s; (3SYjO SdjeGf LHQs; (3eMehO YHOGdQMef eMeOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3jMXi GdTQW GdeGfY ef GdJUQa HCgejI HGdZI ai cdG GdOQGSGJ GdbGfhfjI hGdOQGSGJ GdTQYjI Ydi GdShGA ; hPdc dJYdbI HMb ef Cge GdMbhb GdEfSGfjI hgh GdEfSGf hgh Mb GdEfSGf ai GdJedc hdJYdbI CjVkG HMb GdJUQa GdPj jYO LhgQ GdMb ai GdedcjI (B. (3hbO CMJJ GdQSGdI Ydi aUd JegjOi (B: (3hbSejf QFjSjf hbO egOfG ddHMK HebOeI YGeI Yf Mb GdedcjI hGdbjhO GdJi JQO Ydjg (B:: (3hbO HjfG ai gPg GdebOeI JYQja hNUGFU hYfGUQ Mb GdecdjI(B. (3hcPdc HjfG GdbjhO GdbGfhfjI hGdEOGQjI GdJi JQO Ydjg(B. (3CeG ai GdbSe GdChd abO JYQVfG ai GdHGH GdChd deGgjI GdTQW GdeGfY ef GdJUQa (B: (3hef NdGdg JWQbfG ai aUdg GdChd Edi JYQja GdTQW GdeGfY ef GdJUQa hai GdKGfj JMOKfG Yf eOi eTQhYjI GdTQW GdeGfY ef GdJUQa ai GdbhGfjf GdhVYjI hGdabg GdESdGej(B. (3hCeG ai GdHGH GdKGfj abO JfGhd BKGQ GdTQW GdeGfY ef GdJUQa hLRGA JNdagG(B. (3CeG ai GdbSe GdKGfj abO JfGhdfG BKGQ GdTQW GdeGfY ef GdJUQa (B: (3hLRGA eNGdaJg ai GdJTQjYGJ GdhVYjI hGdabg GdESdGej (B: (3aQCjfG ai GdHGH GdChd CKGQ GdTQW GdeGfY ef GdJUQa (B: (3hef NdGdg JWQbfG Edi BKGQ GdTQW ai GdbGfhf GdhVYj Edi GdeTJQW Ydjg (B: (3hHGdfSHI dOGFfjg (B: (3hJcdefG CjVkG Yf GdBKGQ HGdfSHI ddZjQ (B: (3heOi LhGR GdGMJLGL HGdTQc Ydi GdZjQ (B: (3hPdc ai GdaUd GdChd hai GdaUd GdKGfj hGdNGU HGdabg GdESdGej JWQbfG Edi GdBKGQ GdYGeI ddTQW GdeGfY ef GdJUQa Ke JMOKfG Yf GdBKGQ GdNGUI ddTQWI (B. (3hCNjQkG ai GdHGH GdKGfj JfGhdfG LRGA eNGdaI GdTQW ai cd ef GdJTQjYGJ GdhVYjI hGdabg GdESdGej(B: (3hJcjag GdbGfhfi hGdTQYi (B: (3hPdc ai aUdjf (B: (3NUUfG GdChd dLRG eNGdaI GdTQW GdeGfY ef GdJUQa (B: (3hGdKGfj ddJcjja GdbGfhfj hGdTQYj(B. (3Ke CfgjfG GdQSGdI HNGJeI ChLRfG ajgG Cge GdfJGFL ddHMK hJhUjGJi HgPG GdTCf(B{u(32003(B} s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfj, (B2017s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B256-271s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdeOfjs; (3GdJUQas; (3GdTQW GdeGfYs; (3eOj eTQhYjI GdTQW GdeGfY ef GdJUQas; (3GdbGfhf GdhVYis; (3LRGA JNda TQhW UMI GdTQW GdeGfY ef GdJUQas; (3Mb GdedcjIs; (3eOj eTQhYjI GdTQW GdeGfY ef GdJUQas; (3GdTQW GdHGWds; (3GdGKGQ GdYGeI hGdNGUI ddTQW GdeGfY ef GdJUQas; (3Jcjja GdTQW GdeGfY ef GdJUQas; (3GdJcjja GdbGfhfj hGdTQYjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs